2004
DOI: 10.1071/sr04026
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and chemical factors regulating methane oxidation in a New Zealand forest soil

Abstract: Tropospheric methane (CH 4 ) is oxidised by soil microbes called methanotrophs. We examined them in soil samples from a pristine Nothofagus forest located in New Zealand. Laboratory incubations indicated the presence of high-affinity methanotrophs that displayed Michaelis-Menton kinetics (K m = 8.4 µL/L where K m is the substrate concentration at half the maximal rate). When the soil was dried from its field capacity water content of 0.34 to 0.16 m 3 /m 3 , CH 4 oxidation rate increased nearly 7-fold. The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 53 publications
7
44
1
Order By: Relevance
“…Research on soil-atmosphere CH 4 exchange has been conducted across a range of ecosystems Castaldi and Fierro, 2005;Luo et al, 2013), but assessing the spatial and temporal variability of CH 4 fluxes at the landscape scale has been limited. Studies focused on CH 4 oxidation have shown varied responses to commonly measured environmental variables such as soil moisture and temperature (e.g., Adamsen and King, 1993;Bradford et al, 2001;Price et al, 2004), nutrient variability (e.g., N species: Verchot et al, 2000; dissolved organic carbon: Sullivan et al, 2013). In addition to these physiological constraints, soil structure and texture create the physical landscape at the microbial scale by mediating how quickly soils drain and saturate, directly influencing transport and diffusion of substrates and O 2 (Dorr et al, 1993;Czepiel et al, 1995;Ball et al, 1997;von Fischer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research on soil-atmosphere CH 4 exchange has been conducted across a range of ecosystems Castaldi and Fierro, 2005;Luo et al, 2013), but assessing the spatial and temporal variability of CH 4 fluxes at the landscape scale has been limited. Studies focused on CH 4 oxidation have shown varied responses to commonly measured environmental variables such as soil moisture and temperature (e.g., Adamsen and King, 1993;Bradford et al, 2001;Price et al, 2004), nutrient variability (e.g., N species: Verchot et al, 2000; dissolved organic carbon: Sullivan et al, 2013). In addition to these physiological constraints, soil structure and texture create the physical landscape at the microbial scale by mediating how quickly soils drain and saturate, directly influencing transport and diffusion of substrates and O 2 (Dorr et al, 1993;Czepiel et al, 1995;Ball et al, 1997;von Fischer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sandy texture and generally low water content during the study period could maintain a relatively high CH 4 diffusion rate from the atmosphere to the methanatrophs of soil. Decrease of CH 4 consumption after the application of NH 4 + fertilisers has been reported in many studies (Hutsch et al 1994;Price et al 2004;Wang et al 2004). With the increased applied NH4+-N to the soil from 13 to 96 kg N ha -1 , the percentage of methane oxidation being inhibited increased from 31 to 97% (Price et al 2004).…”
Section: Methanementioning
confidence: 99%
“…Decrease of CH 4 consumption after the application of NH 4 + fertilisers has been reported in many studies (Hutsch et al 1994;Price et al 2004;Wang et al 2004). With the increased applied NH4+-N to the soil from 13 to 96 kg N ha -1 , the percentage of methane oxidation being inhibited increased from 31 to 97% (Price et al 2004). This effect has been attributed to a competition between CH 4 and NH 3 for the same active site on the methane-and ammonia-monooxygenase (Knowles 1993).…”
Section: Methanementioning
confidence: 99%
“…Studies focused on CH4 oxidation have shown varied responses to commonly measured environmental variables such as soil moisture and temperature (e.g. Adamsen and King, 1993;Bradford et al, 2001;Price et al, 2004), nutrient variability (e.g., N species: Verchot et al, 2000; and dissolved organic carbon: Sullivan et al, 2013). In addition to these physiological constraints, soil structure and texture create the physical landscape at the microbial scale by 25 mediating how quickly soils drain and saturate, directly influencing transport and diffusion of substrates and O2 (Dorr et al, 1993;Czepiel et al, 1995;Ball et al, 1997;von Fischer et al, 2009).…”
Section: How Do Environmental Variables Relate To Ch4 Flux Through Thmentioning
confidence: 99%